Joint Associations of Maternal Gestational Diabetes and Hypertensive Disorders of Pregnancy With Overweight in Offspring - Gu, Yuying; Lu, Jun; Li, Weiqin; Liu, Huikun; Wang, Leishen; Leng, Junhong; Li, Wei; Zhang, Shuang; Wang, Shuting; Tuomilehto, Jaakko; Yu, Zhijie; Yang, Xilin; et al. (Frontiers in Endocrinology, 2019)
Objectives: Either maternal gestational diabetes mellitus (GDM) or hypertensive disorder of pregnancy (HDP) is associated with an increased risk of obesity in the offspring. However, their joint associations with obesity in offspring remain unclear. We investigated the joint associations of maternal GDM and HDP with childhood overweight in offspring. Methods: We performed a large study in 1967 mother-child pairs. Maternal GDM was diagnosed according to the 1999 World Health Organization (WHO) criteria. HDP was defined as self-reported doctor-diagnosed hypertension or treatment of hypertension (including gestational hypertension, preeclampsia, sever preeclampsia or eclampsia) after 20 weeks of gestation on the questionnaire. Body mass index (BMI) for age Z-score and childhood overweight were evaluated according to WHO growth reference. We used the general linear models to compare children’s Z score for BMI and logistic regression models to estimate odds ratios of childhood overweight according to maternal different status of GDM and HDP. Results: Offspring of mothers with both GDM and HDP had a higher BMI for age Z-score (0.63 vs 0.03, P <0.001) than children born to normotensive and normoglycemic pregnancy. After adjustment for maternal and children’s major confounding factors, joint GDM and HDP were associated with increased odds ratios of offspring’s overweight compared with normotensive and normoglycemic pregnancy (2.97, 95% confidence intervals [CIs] 1.65-5.34) and GDM alone (2.06, 95% CIs 1.20-3.54), respectively. After additional adjustment for maternal pre-pregnancy BMI and gestational weight gain, joint maternal GDM and HDP was still associated with an increased risk of offspring’s overweight compared with the maternal normotensive and normoglycemic group but became to have a borderline increased risk compared with the maternal GDM alone group. Conclusions: Maternal GDM alone or joint GDM and HDP were associated with increased ratios of offspring’s overweight.